Project and program risk management : a guide to managing project risks and opportunities - Wideman, R. Max (Project Management Institute, 1992)
"This handbook deals with the function of risk management in the context of program or program management. It establishes the need for examining risks or opportunities in project work and describes approaches which can lead to significant reducation of the risk as well as to better project performance." -- Forward.
Keywords: Project management.; Risk management.; elektronické knihy; electronic books